2011
DOI: 10.1371/journal.pone.0024051
|View full text |Cite
|
Sign up to set email alerts
|

A Global Clustering Algorithm to Identify Long Intergenic Non-Coding RNA - with Applications in Mouse Macrophages

Abstract: Identification of diffuse signals from the chromatin immunoprecipitation and high-throughput massively parallel sequencing (ChIP-Seq) technology poses significant computational challenges, and there are few methods currently available. We present a novel global clustering approach to enrich diffuse CHIP-Seq signals of RNA polymerase II and histone 3 lysine 4 trimethylation (H3K4Me3) and apply it to identify putative long intergenic non-coding RNAs (lincRNAs) in macrophage cells. Our global clustering method co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Based on the Refseq genes showing strong co-expression relationship with lincRNAs, a method commonly used for functional prediction of unknown genes3031, we predicted the biological functions for these 37 lincRNAs (see Methods). Enrichment analysis of GO terms and KEGG pathways showed that these down-regulated lincRNAs might be associated with transcriptional regulation, RNA processing and translational elongation processes, etc .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Refseq genes showing strong co-expression relationship with lincRNAs, a method commonly used for functional prediction of unknown genes3031, we predicted the biological functions for these 37 lincRNAs (see Methods). Enrichment analysis of GO terms and KEGG pathways showed that these down-regulated lincRNAs might be associated with transcriptional regulation, RNA processing and translational elongation processes, etc .…”
Section: Resultsmentioning
confidence: 99%
“…Similar to many other RNA molecules, lncRNAs are initially transcribed by Poly II in the nucleus and can be regulated by transcriptional factors (45). NF-kB signaling can regulate both the activation and inhibition of lncRNA expression (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…For example, lincRNA are generally expressed at low or medium levels relative to mRNAs from protein coding genes (Cabili et al 2011;Garmire et al 2011). Thus the mRNA transcriptome and lincRNA transcriptome may yield different levels of power, even when they are generated from the same RNA-Seq experiments and the same biological samples.…”
Section: Differences In Experimental Power Based On Transcript Typementioning
confidence: 99%